Comparison of recombinant and whole cell leptospiral antigen against different cattle serovars of leptospira - PARTHIBAN, M; KUMAR, S SENTHIL; BALAKRISHNAN, G; AARTHI, K S (The Indian Journal of Animal Sciences, 2015)
The outer membrane protein, viz. OmpL1 of Leptospira interrogans Icterohaemorrhagiae was cloned into pET15b vector. The recombinant colonies were expressed in E. coli BL21 DE3 cells. The expressed proteins were checked in SDS-PAGE and western blot analysis. Similarly, the whole cell antigen was prepared using Leptospira interrogans Icterohaemorrhagiae culture. The cross reactivity of recombinant and whole cell leptospiral antigen against 5 different cattle serovars viz., Hebdomadis, Australis, Hardjo, Pomona, and Ballum were tested using ELISA. All the five cattle serovars gave statistically significant values for cross reaction against recombinant antigen in comparison to whole cell antigen. This clearly indicated that in comparison to whole cell antigen OmpL1 an outer membrane protein cross reacted with different cattle serovars and could be used as an effective diagnostic antigen for leptospirosis.